Knotted realities: Understanding what delays early and child marriage for girls in urban slums of Bangladesh - Ahsan, Sairana; Karim, Shuchi; Biswas, Subas; Rashid, Sabina Faiz (Bangladesh Development Initiative, 2022)
This article was published in the Journal of Bangladesh Studies by BDI.The Journal's website is at: https://www.researchgate.net/publication/350813846_Knotted_Realities_Understanding_What_Delays_Early_and_Child_Marriage_for_Girls_in_Urban_Slums_of_Bangladesh